A canonical correlation analysis on the relationship between functional fitness and health-related quality of life in older adults. (January 2017) - Chung, Pak-Kwong; Zhao, Yanan; Liu, Jing-Dong; Quach, Binh
Highlights: There are positive and moderate relationships between overall FF and overall HRQoL in older adults. FF has a significant influence on HRQoL particularly physical functioning dimension. Key FF variables influencing relationship between FF and HRQOL are different between men and women. Abstract: Objective: This study aimed to explore the relationship between the functional fitness (FF) and health-related quality of life (HRQoL) in older adults, and to identify the key subdimensions of FF and HRQoL influencing their overall relationship. Methods: This cross-sectional study was performed among 851 independent community members (65–84 years; men = 402). The Senior Fitness Test and the Short Form 36 Health Survey were used to measure FF and HRQoL, respectively. A canonical correlation analysis was conducted using seven fitness variables as predictors of eight HRQoL variables to examine the relationship between FF and HRQoL. Results: The overall FF was positively correlated with the overall HRQoL in both men (canonical correlation = 0.350) and women (canonical correlation = 0.456). The up-and-go and 2-min step contributed the most to FF, and physical functioning contributed the most to HRQOL among men. Conversely, the up-and-go and 30-s chair stand contributed the most to FF, and physical functioning contributed the most to HRQoL in women. Conclusions: There were positive and moderate relationships between overall FF and overall HRQOL in older adults. The FF has a significant influence on HRQoL, particularly physical functioning. The main FF components influencing the relationship between FF and HRQoL in men are balance and agility and aerobic endurance, whereas in women they are balance and agility and lower extremity muscle strength. Results from this study facilitate comprehensively understanding the relationship between FF and HRQoL, and generating critical insight into HRQoL improvement from the perspective of FF enhancement.